2017
DOI: 10.1007/s13629-017-0186-z
|View full text |Cite
|
Sign up to set email alerts
|

Initiatief Comprehensive Prostate Cancer Network (CPCN) in Zuidoost Nederland

Abstract: Samenvatting De huidige diagnostiek en behandeling van prostaatkankerzorg is complex. Zeker complexe interventies, zoals robotprostatectomie, vragen om concentratie, teneinde een goed meetbaar optimaal kwaliteitsniveau te kunnen behalen. Volume is noodzakelijk om kortcyclische kwaliteitsverbeteringen te kunnen implementeren en evalueren. Tevens is volume nodig om een doorlopend inzicht te geven aan alle betrokken medische en verpleegkundige zorgprofessionals en om een optimale logistieke en kwaliteitsstructuur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In 2013, two hospitals (Catharina Hospital Eindhoven, Eindhoven, The Netherlands [CHE] and Canisius Wilhelmina Hospital, Nijmegen, The Netherlands [CWH]) decided to collaborate and concentrate their RARP procedures in a single location (CWH) [15] . Between March 2013 and July 2016, 125 men with PCa diagnosed in CHE who were eligible for RP were referred to CWH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, two hospitals (Catharina Hospital Eindhoven, Eindhoven, The Netherlands [CHE] and Canisius Wilhelmina Hospital, Nijmegen, The Netherlands [CWH]) decided to collaborate and concentrate their RARP procedures in a single location (CWH) [15] . Between March 2013 and July 2016, 125 men with PCa diagnosed in CHE who were eligible for RP were referred to CWH.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of these data, the Dutch Society of Urology increased the minimal annual number of RARP procedures per hospital to 100 in January 2019. To meet the volume standard of 100 procedures, networks and partnerships between hospitals have been formed in which RARP procedures are concentrated at one location [15] . One of the challenges for these collaborations is the uniformity of the diagnostic workup and the indication for RARP.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,11 The eld of video review and postoperative results analysis is focused on predicting postoperative results and reducing complications. 1,2,12,13 Even though multiple groups have investigated the possibility of video review it is unclear if video review has found its place in daily clinical practice. Earlier research of our group has shown Dutch experts are willing to participate in surgical video review.…”
Section: Introductionmentioning
confidence: 99%